Pegon Arabic as a Medium for Mastering Mufradat among Santri: Pegon Arab sebagai Media untuk Menguasai Kosakata di Kalangan Santri - Fikri R, Syahensyah Raiq El; Moch. Bahak Udin By Arifin (Indonesian Journal of Islamic Studies, 2025)
General Background: Arabic learning among santri in Islamic boarding schools is often limited by difficulties in mastering mufradat (vocabulary), which affects their comprehension of classical Islamic texts. Specific Background: Pegon Arabic—Arabic script used for writing Javanese—has long been a linguistic bridge in traditional Islamic education, yet its pedagogical potential remains underexplored in modern learning contexts. Knowledge Gap: Few empirical studies examine how Pegon Arabic contributes to vocabulary mastery within contemporary pesantren environments. Aims: This study investigates the role of Pegon Arabic in improving mufradat mastery among santri at Al-Fattah Sidoarjo. Results: Findings indicate that the application of Pegon Arabic facilitates more effective vocabulary retention and contextual understanding, supported by the learners’ familiarity with the Javanese linguistic structure. Novelty: The study recontextualizes a traditional writing system as a modern pedagogical strategy, merging cultural heritage with language instruction. Implications: This approach offers an innovative pathway for Arabic educators to integrate local linguistic identities into curriculum design, enhancing linguistic accessibility and learning outcomes among santri. Highlights: Pegon Arabic strengthens contextual understanding of mufradat. Integrates cultural identity in Arabic language learning. Revitalizes traditional scripts for modern educational practice. Keywords: Pegon Arabic, Mufradat Mastery, Santri, Islamic Education, Vocabulary Learning